Scientific-Cum-Doctriner dalam Studi Islam Menurut Mukti Ali : Studi Analisis Perspektif Worldview Islam - Fadhilah, Manzilatul; Trisnani, Asif; Awaludin, Asep (Jurusan Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Adab UIN Sultan Maulana Hasanuddin Banten, 2022)
This article tries to reveal Mukti Ali's thoughts about his new approach in Islamic Studies, namely Scientific-Cum-Doctrinaire in the eyes of Islamic Worldview. This article was written using a qualitative research approach by taking the type of library research, in which the data analysis technique was descriptive-qualitative. The results of the study were also explored through a philosophical approach to examine the thoughts of Mukti Ali who was able to create his own method of understanding Islam, namely the synthesis method and the typological method. The result of this research is that the Scientific-Cum-Doctrinaire approach is the result of a combination of three different approaches. First, Doctrinaire or dogmatic, namely approaching religion based on the statements of the Qur'an and Hadith, but this approach is considered outdated by Mukti Ali because it cannot be applied in society. Second, Scientific, which is approaching religion scientifically. However, Ali rejects this approach if it is only used singly because it is considered unsuitable. Third, synthesis is a combination of Scientific-Doctrinaire. According to him, this approach is appropriate to use in understanding Islam. Meanwhile, in the Islamic worldview, the most perfect method is the monotheistic method. Furthermore, the concept of Scientific-Cum-Doctrinaire in the eyes of the Islamic worldview is value-free. Mukti Ali also admitted that the steps of the Scientific-Cum-Doctrinaire method had not been clearly defined, thus, the Scientific-Cum-Doctrinaire method was different or incompatible with the Islamic worldview concept.